Processo de avaliação de desempenho dos servidores técnico-administrativos da Universidade Estadual da Paraíba (UEPB) - Pita, Ubiramar Sinfrônio (2018)
This research analyzed the process of performance evaluation, from the perspective of the technical-administrative and the managers of the evaluation process, at the Universidade Estadual da Paraíba (UEPB). In the Brazilian public administration, the performance evaluation acquired relevance in the context of the emergence of the administrative model from the Bresser-Pereira State Reform Plan of the State Apparatus (BRASIL, 1995). In the Federal Institutions of Higher Education, the Lula Government structured the career plan of the Administrative Technicians in Education, linking the development of the career server to the progression through professional qualification and professional merit, the latter accompanied by performance evaluation. In the case of UEPB, the creation of the regulation of the evaluation process in 2010. The objective of this research was to analyze the process of performance evaluation of technical-administrative at UEPB. It was a predominantly qualitative research; exploratory and descriptive as to the ends, as well as bibliographical and field research as to the means, being a case study. It was carried out in the UEPB, with the technical-administrative servers and professionals involved in the management of the evaluation process. For data collection, we used documentary analysis and interviews, analyzed through thematic content analysis. The following objectives of UEPB evaluative process were assessed: management of the technical-administrative career, performance improvement of its employees, improvement of the public service and implications of the evaluation in the actions and institutional policies. The purpose incident of progression by length of service and stability in the job, while serving as a stimulus to server development in his career, relegates the focus on improving server performance tied to organizational goals. In addition, there was a low correlation between the results of the performance evaluation and other institutional actions. The institution does not adequately appropriate the performance appraisal to make it an instrument of people management allowance. This study allowed understanding, beyond its legal universe, how the evaluation process works at UEPB, as well as the real purposes of the performance evaluation, which can facilitate to the different professionals, an evaluation of this instrument of the management of people committed to the technicians desires.